Letter (copy) : Food for Spain - Tewson, Vincent
030-0208-001 HVT/FC/220. Secretary's. 7th February, 1938. Mr. W. Schevenels, The International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS, VIIe. Dear Mr. Schevenels, FOOD FOR SPAIN. I am enclosing herewith for your information a copy of the invoice for the goods shipped per the s.s. "Plover". I am forwarding you this in order that you may have full details of what has been sent. In addition to the amount shown on the invoice there is an item of nearly £200 for freight charges, insurance and incidentals, so that the total amount to be paid will be in the region of £2,580. Yours sincerely, Assistant Secretary. Copy of Invoice. 292/946/30/208